“Lucas” in the Laboratory - ASPAROUHOVA, ELENA; BOSSAERTS, PETER; ROY, NILANJAN; ZAME, WILLIAM (Journal of Finance, 2016)
ABSTRACT We study the Lucas asset pricing model in a controlled setting. Participants trade two long‐lived securities in a continuous open‐book system. The experimental design emulates the stationary, infinite‐horizon setting of the model and incentivizes participants to smooth consumption across periods. Consistent with the model, prices align with consumption betas and comove with aggregate dividends, particularly so when risk premia are higher. Trading significantly increases consumption smoothing compared to autarky. Nevertheless, as in field markets, prices are excessively volatile. The noise corrupts traditional generalized method of moment tests. Choices display substantial heterogeneity, with no subject representative for pricing.